Anterior Mandibular Lingual Foramina: An In Vivo Investigation. (25th August 2014) - Bernardi, Sara; Rastelli, Claudio; Leuter, Cinzia; Gatto, Roberto; Continenza, Maria Adelaide
Abstract : In descriptions of surgical procedures in mandible, often there is no mention of an anatomical variance, the genial spinal foramina, where nerves and vessels go through. Aim of this study is to investigate frequency, shape, and dimensions of these foramina. 56 computed tomography dentascans were analyzed with an implant planning software. The considered parameters were frequency, number, position, diameters, and length of canals; the collected data were inserted in a spreadsheet and statistically analyzed; therefore, they were compared with those found in the literature. The measurements agree with the ones found in earlier studies, except for the length of the inferior spinal canals, which resulted lesser than that found in the literature. The frequency of the inferior spinal foramina, the data related to the inferior spinal foramina diameter (cross scan), and the measurements related to the superior spinal foramina diameter (axial scan) resulted to be major compared to those reported in literature. These obtained results are clinically interesting because an implant planning software has been employed, daily used by operators, and that permits in vivo investigations. Furthermore, due to the possibility of hemorrhagic accidents in this mandibular region, these data are particularly interesting for all of the operators who make interventions in this area.